Method of biomechanical analysis of kicks of the main course in acrobatic rock'n'roll - Petrо Kysym; Natalia Batieieva (Слобожанський науково-спортивний вісник, 2017)
Purpose: biomechanical analysis of kicks of the main course in acrobatic rock'n'roll. Material & Methods: following research methods were used: theoretical analysis and generalization of data from special scientific and methodological literature; pedagogical observation; biomechanical computer analysis; video footage of the finals of World championships, Europe championships, Cup of Ukraine (2017) in acrobatic rock and roll. Result: biomechanical analysis of the kicks of the main course by qualified athletes was conducted; kinematics characteristics (path, speed, acceleration, effort) of the center of mass (CM) biolinks of the athlete’s body (male partner, female partner) were obtained: feet, shins, hips. The energy characteristics are determined – mechanical work and kinetic energy of the legs links when performing the kick of main course. Conclusion: it is established that the method of biomechanical analysis of the kick of the main course performance significantly affects the level of technical training of qualified athletes in acrobatic rock and roll.